Computer Exhumation in the Daniel Moyano Virtual Archive. A Reflection about Writing Formats, Materiality and the Evolution of Originals and Drafts (2016)
This paper addresses central notions concerning writer’s archives, based on an experiment conducted in the Daniel Moyano Virtual Archive: the recovery of texts from an outdated computing device. These texts were preserved by Moyano in a storage media inaccessible for present times, and were recovered in a joint effort between the CRLA-Archives (France) and the National University of Cordoba (Argentina). From a hermeneutical perspective, computer exhumation of these documents allowed us to articulate the genesis of the author ́s processes of fictionalization -not restricted to texts considered literary at first glance- with a socio-technical interrogation about these practices. This has inspired questions about the transformation of role of technique, particularly in the relation between art and society